MEASURING INFLUENCEUNDERSTANDING OF ISAK 35 ON THE PREPARATION OF MOSQUE FINANCIAL REPORTS - Abdul Halim; Syawal Harianto; Haris Al Amin (CV. Radja Publika, 2023)
This study aims to determine the effect of understanding ISAK 35 on the desire of management in preparing financial statements for mosques in Kota Juang Bireuen sub-district. This research is a quantitative research using primary data in the form of the results of filling out questionnaires and interviews with mosque administrators in Kota Juang Bireun District. The model used in this study is a simple linear regression model with a sampling technique based on the census, with a sample of 60 mosque management respondents in Kota Juang Bireuen District. The results showed that there was a significant influence between the independent variables, i.e. Understanding of ISAK 35 (X1) on the dependent variable, namely the Preparation of Financial Statements (Y) with a t count value of 0.509 > t table of 0. 235 and with a value of Sig. of 0.000 <0.05 which means that the independent variable, namely understanding of ISAK 35 (X1), has an influence on the dependent variable, namely the preparation of financial statements (Y). The test results for the Coefficient of Determination are indicated by the R Square value of 0.299 which illustrates that there is a not so strong influence between the independent variables namely Understanding of ISAK 35 (X1) on the dependent variable namely Preparation of Financial Statements (Y), this is due to a weak understanding of the concept ISAK 35 for mosque administrators in Kota Juang Bireun District, and training and guidance received by administrators has not been optimal so that the level of understanding of ISAK 35 for mosque administrators needs to be increased. 05 which means that the independent variable, namely Understanding of ISAK 35 (X1), has an influence on the dependent variable, namely the Preparation of Financial Statements (Y).